(untitled) (Italian Review of Legal History, 2019)
The Author analyzes the Italian racial laws within the perspective of Constitutional Law. Alongside a detailed recognition of the laws enacted from the colonial period till those enforced during the so-called Republic of Salò, the Author examines and discusses the notion of race and its meanings. The Author investigates the meanings attributed to the notion of race between the Fascist Regime and the Constitution, highlighting the path where the notion of race moved from being considered as a biological factor of division among human beings to a symbol of a rejected past, inherent in the constitutional principle of racial equality. The Author does not omit to focus on the debate developed at the supranational level at the outset of World War II to the recent conversation as to the opportunity to challenge the explicit reference to the notion of race within Article 3 of the Italian Constitution.